When political science championed public service training: the American political science association campaign for professional public administration - Schachter, Hindy Lauer (2007)
This article examines how Progressive-Era political scientists worked to promote public service training. it gives evidence that the Progressive-Era political science community had a broad view of its mission that included preparing civil servants. Since World War II, tension has permeated relations between mainstream political science and professional public administration programs. Participants in current debates on relations between the two fields can gain from knowing something about the broad interests that engrossed the American Political Science Association at its start. - Reproduced.
Keywords: Civil service; Training